Saman dan Bines : Pertemuan Tari Tradisi Pada Peristiwa Budaya Bejamu Saman di Gayo Lues, Aceh - Sabri Gusmail; Fifie Febryanti Sukman; Prasika Dewi Nugra (Mahesa Research Center, 2020)
Saman and Bines dance is a traditional art from Gayo Lues, a very inherent existence in the supporting community as a dance that is specifically danced by men for Saman and women for Bines. In this article, the author describes the presentation of the arts at the Bejamu Saman cultural event. As a cultural heritage, the presentation of Saman and Bines in Bejamu Saman activities is the focus of research, how to present Saman and Bines in Bejamu Saman cultural events. This research uses qualitative methods, namely data that has been collected in the field regarding the Saman and Bines dance on Bejamu Saman activities and other data related to the object and focus of the research. The data obtained were then analyzed descriptively-analytically with a textual analysis approach. The purpose of this research was to describe the presentation form of the Saman and Bines dance in Bejamu Saman activities. So that the results of this research can be used as supporting material in future Saman and Bines dance research. Understand the differences in the presentation of Saman and Bines as a spectacle and or as a series of cultural activities. Obtain information related to Bejamu Saman, a cultural event of the Gayo Lues community that represents the social identity of the Gayo Lues community in a reflection of the nation's character.